2016
DOI: 10.1101/089847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

fMRI Correlates of Reaction Time Prolongation during intentional False Responding; an inter-individual difference study

Abstract: 22Reaction time (RT) is chiefly longer when people lie. However, the baseline speed in answering 23 questions and the amount of RT prolongation during lying show considerable amount of inter-individual 24 variability. In the current study, we exploited this fact to glean insights on the contribution of each lie-25 related brain region to hampering of response speeds when people try to be deceitful. In an event-related 26 fMRI session, participants were interrogated by yes-no autobiographical questions and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, this study is the first to provide a direct empirical examination on the neural underpinnings associated with spontaneous deception and truth-telling. While past neuroimaging studies have shown the DLPFC and VLPFC to be consistently activated during deception (Abe et al, 2006;Ito et al, 2012;Lee et al, 2010;Peth et al, 2015;Pishnamazi et al, 2016), and some studies showing IPL activation for deception (Cui et al, 2014;Kireev et al, 2013;Nose, Murai, & Taira, 2009), activities in these frontoparietal brain regions were also found for truth-telling (Yin et al, 2016). Activation of the frontoparietal regions for spontaneous truth-telling was attributed to decision making and cognitive control when facing with a temptation to deceive.…”
Section: Spontaneous Deception and Truth-telling By Yin Et Al (2016)mentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, this study is the first to provide a direct empirical examination on the neural underpinnings associated with spontaneous deception and truth-telling. While past neuroimaging studies have shown the DLPFC and VLPFC to be consistently activated during deception (Abe et al, 2006;Ito et al, 2012;Lee et al, 2010;Peth et al, 2015;Pishnamazi et al, 2016), and some studies showing IPL activation for deception (Cui et al, 2014;Kireev et al, 2013;Nose, Murai, & Taira, 2009), activities in these frontoparietal brain regions were also found for truth-telling (Yin et al, 2016). Activation of the frontoparietal regions for spontaneous truth-telling was attributed to decision making and cognitive control when facing with a temptation to deceive.…”
Section: Spontaneous Deception and Truth-telling By Yin Et Al (2016)mentioning
confidence: 98%
“…The functional involvement of DLPFC for working memory (Cohen et al, 1997), VLPFC for response inhibition (Rubia et al, 2001;Rubia, Smith, Brammer, & Taylor, 2003), and lateral PFC (found in the DLPFC) for task switching (Dove, Pollmann, Schubert, Wiggins, & Von Cramon, 2000) have also been well established in non-deception studies. As far as deception is concern, significant activations consistently observed in the DLPFC and VLPFC would highlight the involvement of executive function in deception (Ito et al, 2012;Pishnamazi, Doost, Ganjgahi, Ekhtiari, & Oghabian, 2016;Priori et al, 2008;.…”
Section: Lateral Prefrontal Cortex: Executive Functionmentioning
confidence: 99%